Management of an early anastomotic stricture using the Seldinger technique - Kehagias, Dimitrios; Mulita, Francesk; Anagnostopoulos, Fotios; Kehagias, Ioannis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
The most common cause of benign stenosis in the large intestine is the anastomotic stricture, which occurs in 5–20% after colorectal resection [1, 2]. The term anastomotic stricture refers to the narrowing of the intestine, which results in clinical symptoms of complete or partial intestinal obstruction [3]. The predisposing factors for this serious complication are not clearly understood, but anastomotic leakage, preoperative radiation, and ischaemia due to excessive tension in the anastomosis correlate with increased incidence [4]. Anastomotic strictures often concern interventions in the middle or low rectum, and they usually self-improve over time [5]. Nevertheless, persistent strictures will require intervention such as endoscopic- or fluoroscopy-guided dilatation, stenting, reoperation, or incision of the stricture with diathermy during endoscopy [6]. Anastomotic strictures in the early postoperative period are rarely reported in the bibliography, and they are usually observed at a median 5–12 months following surgery [7]. Early anastomotic stricture is defined as a stricture that requires intervention within 6 weeks of gastrointestinal anastomosis creation [8]. We present the case of a female patient who developed an anastomotic stricture following right colectomy for colon cancer and on the 14th postoperative day. After a failed endoscopy, she underwent anastomotic dilatation under fluoroscopic guidance with alleviation of symptoms.